A Critical Precursor Frequency of Donor-Reactive CD4(+) T Cell Help is Required for CD8(+) T Cell-Mediated CD28/CD154-Independent Rejection - Ford, Mandy L. (2008)
Antigen-specific precursor frequency is increasingly being appreciated as an important factor in determining the kinetics, magnitude, and degree of differentiation of T cell responses, and recently was found to play a critical role in determining the relative requirement of CD8(+) T cells for CD28- and CD154-mediated costimulatory signals during transplantation. We addressed the possibility that variations in CD4(+) T cell precursor frequency following transplantation might affect CD4(+) T cell proliferation, effector function, and provision of help for donor-reactive B cell and CD8(+) T cell responses. Using a transgenic model system wherein increasing frequencies of donor-reactive CD4(+) T cells were transferred into skin graft recipients, we observed that a critical CD4(+) T cell threshold precursor frequency was necessary to provide help following blockade of the CD28 and CD154 costimulatory pathways, as measured by increased B cell and CD8(+) T cell responses and precipitation of graft rejection. In contrast to high-frequency CD8(+) T cell responses, this effect was observed even though the proliferative and cytokine responses of Ag-specific CD4(+) T cells were inhibited. Thus, we conclude that an initial high frequency of donor-reactive CD4(+) T cells uncouples T cell proliferative and effector cytokine production from the provision of T cell help. This is an author-produced version of a manuscript accepted for publication in The Journal of Immunology (The JI). The American Association of Immunologists, Inc. (AAI), publisher of The JI, holds the copyright to this manuscript. This version of the manuscript has not yet been copyedited or subjected to editorial proofreading by The JI; hence, it may differ from the final version published in The JI (online and in print). AAI (The JI) is not liable for errors or omissions in this author-produced version of the manuscript or in any version derived from it by the U.S. National Institutes of Health or any other third party. The final, citable version of record can be found at www.jimmunol.org